PERANAN PENGINDERAAN JAUH DALAM MENYOKONG KAJIAN PEMETAAN BATAS WILAYAH DARAT (STUDI KASUS: DESA BATURETNO, KECAMATAN BANGUNTAPAN, KABUPATEN BANTUL, DIY) - Ahmad, A G (UI Scholars Hub, 2017)
Border mapping is an activity which could be done continuously as the region develops. Many kinds of methods in border mapping have been done, and each has strength and weakness. Technology of remote sensing which continues to develop can be used to optimize border mapping to be more efficient. Remote sensing is one of the way to know the condition of earth surface, which in border mapping uses high resolution image, Quickbird image. The spatial accuracy of Quickbird image which reaches 2.4 meters per pixel can be used to monitor land use, to be created into a map which gives various basic spatial information. Border search that has been agreed on is done on the image, meanwhile field activity is done as additional information in border search. Three sample points that is taken during the research show that remote sensing information that is got can support regional border search because there are differences between BPS data and automatic calculation result according to real regional border, where the area reaches 24 hectares. The study using Quickbird image can be optimized for regional border search on land which has homogenous physical condition.